2017
DOI: 10.1194/jlr.m074443
|View full text |Cite
|
Sign up to set email alerts
|

Diacylglycerol kinase ε deficiency preserves glucose tolerance and modulates lipid metabolism in obese mice

Abstract: Diacylglycerol kinases (DGKs) catalyze the phosphorylation and conversion of diacylglycerol (DAG) into phosphatidic acid. DGK isozymes have unique primary structures, expression patterns, subcellular localizations, regulatory mechanisms, and DAG preferences. DGKε has a hydrophobic segment that promotes its attachment to membranes and shows substrate specificity for DAG with an arachidonoyl acyl chain in the sn-2 position of the substrate. We determined the role of DGKε in the regulation of energy and glucose h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…The presence of multiple DGKs suggest isoform-specific physiological roles for individual DGK isoforms. For example, DGK deficiency is associated with peripheral insulin resistance and obesity (8), whereas DGK ablation preserves glucose tolerance and modulates lipid metabolism (30). The opposing metabolic phenotypes observed between these KO models further reinforce that notion that isoform-specific actions of DGK may influence metabolism.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…The presence of multiple DGKs suggest isoform-specific physiological roles for individual DGK isoforms. For example, DGK deficiency is associated with peripheral insulin resistance and obesity (8), whereas DGK ablation preserves glucose tolerance and modulates lipid metabolism (30). The opposing metabolic phenotypes observed between these KO models further reinforce that notion that isoform-specific actions of DGK may influence metabolism.…”
Section: Discussionmentioning
confidence: 67%
“…In contrast to other DGK isoform-specific KO mouse models including DGK, DGK, and DGK (8,30,49), the metabolic phenotype of DGK KO mice is subtle. Several of the assays utilized in this study have also been applied to other DGK isoform-specific KO mouse models.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…In skeletal muscles, no changes in insulin signaling or glycogen deposition were induced in DGKe 2/2 mice. Recently, Mannerås-Holm et al (47) performed lipidomic analysis in skeletal muscle of HFDfed DGKe 2/2 mice. The authors found that elevated unsaturated and saturated DG species in DGKe-deficient skeletal muscle, although insulin sensitivity remained unaltered in this tissue.…”
Section: Discussionmentioning
confidence: 99%